PQ Theory-Based Control of Single-Stage V2G Three-Phase BEV Charger for High-Voltage Battery. Issue 29 (2019) - Rachid, Aziz; Fadil, Hassan El; Koundi, M.; Idrissi, Z. El; Tahri, A.; Giri, Fouad; Guerrero, J.M.
Abstract: This work dealt with a modeling and a PQ theory-based control of a vehicle-to-grid (V2G) three-phase battery electric vehicle (BEV) charger. This studied system consists of a bidirectional ac-dc three-phase power converter associated with an EV battery pack via an LC filter. The control of the studied system is performed in order to meet all control objectives, namely: (i) Guaranteeing a unity power factor (UPF) during the grid-to-vehicle (G2V) operating mode; (ii) Regulating the reactive power injected during the V2G operating mode; and (iii) Ensuring the battery charging and the battery discharging, safely. To achieve all these objectives, a backstepping controller using the PQ theory has been designed. Therefore, an imbricate-loops structure has been adopted to regulate the reactive power injected into the power grid and to ensure the charging and discharging of the battery. The achievement of all the objectives of the proposed nonlinear controller was confirmed by numerical simulations performed using the MATLAB/Simulink software.